Design and Simulation Analysis of Flexible Joint SEA of Manipulator - Zhang Zijian Du Yunpeng Han Shaojie Shang Kai Zuo Kungang Dong Yangyang (Jixie chuandong)
Series Elastic Actuator （SEA） can effectively improve the flexibility of the joint. However, SEA has the disadvantage of strong nonlinearity of force and deformation. In order to improve the linearity of SEA, a curved beam model with double-ring connection is established, and the stress formulas of different points of the beam model are got by using the normal stress formula of the origin of the axis section, so as to design and verify the series elastic actuator which conforms to the flexible joint. Secondly, the model of the series elastic actuator is simulated and analyzed, and seven points are selected to compare the model with the actual stress. Finally, ANSYS is used to simulate and analyze the strength and deformation of each joint，which effectively guarantees the linear characteristics of SEA and improves the mechanical properties of flexible joint.